A Case Study for Potential Process Improvements in the Briquette Industry - Ahmad Zainuddin, Ahmad Hazly; Hashim, Mohd Yussni (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Biomass briquettes are compressed biomass in the form of blocks or logs. Briquettes can be made from biomass material to make renewable energy fuel. Biomass can be obtained from agricultural waste, wood, and other organic waste. This study looks at the briquette industry in Malaysia to identify potential improvements in the industry. This study also identified the briquette production process and the issues or challenges faced. First of all, existing literature is analyzed involving developments, processes, materials, machines, issues, and challenges. To identify advancements in the briquette sector, this study uses qualitative methods such as site visits and interviews. A company based in Perak was selected as a company in this study. The observation of this company uses rice husk as a raw material to produce briquettes and does not use any additional material. Briquette specifications are produced with strength reaching 1000 kg/cm2, a calorific value of 5000 kJ/kg, and a carbon content of 35%. This briquette manufacturing process uses a screw extrusion machine and the type of screw used is pellets. To identify areas for improvement, the site visit results are compared to the findings from previous studies. As to this study, using biomass materials instead of conventional ones can help Malaysia cut down on waste and pollution. During the site visit, several issues and challenges were found and possible solutions were listed. In conclusion, this study successfully achieved its objectives by identifying the briquette manufacturing process and highlighting the current issues and challenges within the industry. Moreover, the study proposed potential improvements for the briquette manufacturing process, offering valuable insights for enhancing efficiency and addressing existing challenges in the field. The findings of this research contribute to a better understanding of the briquette manufacturing industry and provide a foundation for future advancements and optimizations in the production process.